PENINGKATAN JANGKAUAN PASAR USAHA MIKRO, KECIL DAN MENENGAH (UMKM) PISAU BUKIT JATI MELALUI STATUS WHATSAPP DAN SIMULASI SEBAGAI RESELLER - Ida Ayu Putu Febri Imawati; I Wayan Dika; Ni Made Kariati; Ni Luh Gede Ambaradewi; I Kadek Juni Arta; I Nyoman Bagus Suweta Nugraha (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
This service program aims to increase the market reach of UMKM metal products, especially various types of knife products, through WhatsApp media. WhatsApp was chosen because it is an application that UMKM players and the general public can easily use. This activity was carried out with one local Bukit Jati UMKM, utilizing a training assistance approach and simulating marketing strategies through resellers on WhatsApp social media. The results of the activity indicate that WhatsApp can be a viable promotional tool for reaching consumers in the local and regional areas of Bali Province. Marketing through WhatsApp social media also enables the building of a more personalized relationship between sellers and consumers.